Human-robot interaction: The hospitality experience of young people in hotels that use robots - Andreea Fortuna Schiopu; Ana Mihaela Padurean; Ana-Maria Nica; Valentin Toader; Remus Ion Hornoiu; Maria Cordente Rodriguez (Amfiteatru Economic, 2024)
The past years have brought an accelerated use of robots in the hospitality industry to perform several tasks (i.e., front-desk, cleaning, and check-in, among others). In addition to advantages such as better productivity or lower labour shortages, the use of robots in hotels can enhance the tourist experiences. In this context, this study aims to examine some important antecedents of experience of hospitality in hotels that use robots and of behavioural intention to visit these hotels. We extended a framework used in hospitality to include the use of technology (i.e., robots) and describe the human-robot interaction. The data was collected through an online survey and analysed through structural equation modelling (SEM). The findings show that, when hotels use robots, their perceived ability to be experienced as inviting, careful, and comfortable influence the overall experience of hospitality. These antecedents explain 84% in the variance of the overall experience of hospitality in such hotels. Furthermore, the hospitality experience determines to a very high degree the intention behavioural to visit these hotels. Last but not least, robot anxiety negatively affects the perceived ability of hotels to be perceived as inviting, careful, and comfortable. Tourists who are robot anxious think hotels that use robots are less capable of offering positive experiences. These findings bring new theoretical and practical insights that can be employed to adapt the activities of hotels that use robots to appropriately deliver their service. The model confirms the influence of the aforementioned factors on the experience of hospitality in the technological context, developing the literature related to the use of robots in hotels. Furthermore, managers interested in investing in the use of these devices to improve the guest experience can become more knowledgeable about the opportunities (developing the ability to be perceived as inviting, careful, and comfortable) and challenges (reducing robot anxiety).
Keywords: O33; Z30; 330; human-robot interaction; robots used in hotels; robot anxiety; experience of hospitality; intention to visit hotels that use robots